The Discriminative Validity of the McGill Ingestive Skills Assessment. (1st June 2013) - Francis-Bacz, Charmine; Wood-Dauphinee, Sharon; Gisel, Erika
ABSTRACT: Purpose : The extent to which the McGill Ingestive Skills Assessment can discriminate between known/extreme groups of individuals with or without dysphagia and stroke was determined. Methods : Twenty-four patients with stroke and no dysphagia, eating a regular diet, and 17 patients with stroke and dysphagia, permitted only purees, participated in this study. Using the McGill Ingestive Skills Assessment and a chart review, groups were compared on sociodemographic and clinical characteristics. Univariate tests were performed to examine the significance of between-group differences. Results : The McGill Ingestive Skills Assessment was able to discriminate between two groups of individuals with stroke who have different ingestive abilities based on age and severity of stroke. Conclusion : Results support the clinical usefulness of the tool for dysphagia management in stroke. Further studies are necessary to address the responsiveness of the McGill Ingestive Skills Assessment.